A novel capsule-like structure of micro-sized particles formed by phytosterol ester and γ-cyclodextrin in water. (1st November 2016) - Sasako, Hiroshi; Kihara, Fukashi; Koyama, Kazuo; Higashi, Kenjirou; Yamamoto, Keiji; Moribe, Kunikazu
Highlights: PSE/γ-CD particles prepared by homogenisation have a novel capsule-like structure. A hydrophilic PSE/γ-CD inclusion complex surrounds the hydrophobic free PSE. The PSE/γ-CD inclusion complex had a tetragonal-columnar structure. The PSE/γ-CD weight ratio in the inclusion complex was determined to be 1:5.1. Abstract: The composite material formed by phytosterol ester (PSE) and γ-cyclodextrin (γ-CD) disperses readily in water and has been used to mask undesirable flavours. This paper elucidates the structure of the PSE/γ-CD particle. Cryogenic scanning electron microscopy and contact angle measurements showed that the PSE/γ-CD particles formed a capsule-like structure with a hydrophilic surface. A phase-solubility study using cholesteryl oleate (ChO), one of the components of PSE, showed that ChO formed a hydrophilic and stoichiometric inclusion complex with γ-CD at a molar ratio of 2:5. The structure of the PSE/γ-CD inclusion complex was similar to that of ChO/γ-CD, based on differential scanning calorimetry and powder X-ray diffractometry results. Thus, we propose that the PSE/γ-CD particle has a capsule-like structure wherein a hydrophobic PSE droplet is surrounded by an outer layer of the hydrophilic PSE/γ-CD inclusion complex.